Transmisi Asimetris Harga Tandan Buah Segar (TBS) Domestik dengan Harga Crude Palm Oil (CPO) Pasar Domestik - Varwasih, Mia Wananda; Sandra, Indah Kartika; M, Julia Mardalisa (Universitas Galuh, 2025)
Indonesia is the largest exporter of Crude Palm Oil (CPO) in the world, but global CPO prices are more influenced by demand from large countries and fluctuations in the Rotterdam market. This has an impact on the domestic price of Fresh Fruit Bunches (FFB) received by farmers, which follows the movement of CPO prices. This research aims to analyze the transmission of domestic FFB prices to CPO prices in the domestic market. The data used is secondary time series data of monthly FFB and CPO prices for 12 years (January 2010-December 2021), using the Asymmetric Error Correction Model (AECM) method. The results of the analysis show that there is asymmetric price transmission between domestic FFB prices and domestic CPO, where a decrease in CPO prices is not always followed by a decrease in FFB prices. When domestic CPO prices rise, domestic FFB prices take longer to follow the increase, whereas when CPO prices fall, FFB price adjustments occur more quickly.